Optical, electrical, structural, and morphological properties of KAl4Si2O12/Mg3Si2O9/Fe2O3 clay mineral from Machado mountain region, Tarairá, Colombia (2022)
Physical properties of clay minerals are essential in the evaluation for applications and new potential uses of geological materials. This study presents results of optical, electrical, structural, compositional and morphological analysis of Hillite (0.967) / Chlorite (0.013) / Hematite (0.02) clay mineral extracted from the Machado mountain region in the municipality of Tarairá, department of Vaupés, Colombia. The extracted clay was subjected to treatments to separate it from the others geological compounds before the characterization process. The observed platy morphology allowed to perform a size grain analysis which confirmed the clay-extraction. Particles with 0.8- 1.4 mm diameter and two pseudo-modes distribution in the area histogram were found. The bimodal distribution is assumed to be caused due to the differences between periodic ages of formation of the minerals in the extraction region. Structurally, we found a monoclinic structure with residues of triclinic polymorphous and Hexagonal scalenohedral segregated structures. The XRD analysis was based in the EDS measurements, given the stoichiometry of the sample. Also, a big absorption in the optical UV-range with an effective band gap in the clay to 2.852(8) eV was found. The electrical properties of the clay showed a strong non-linear insulator behavior. Electrical losses by polarizing the sample were decreased by a previous heating. Finally, the complete physical properties analysis allowed to introduce this material as an inexpensive, time efficient insulator.